2009
DOI: 10.5539/mas.v3n2p147
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Performance of Quarry Waste in Flowable Fly Ash-Gypsum Slurry

Abstract: Mining the sand, from riverbed is hazardous to environment. The deep pits dig in the riverbed for sand mining effects on ground water level and erode the nearby land. Most of the provincial Governments in India have imposed ban on mining sand from riverbeds. In such a situation the quarry waste can be an alternative to river sand .The present paper deals with the experimental investigation on the performance of quarry waste in fly ash gypsum slurry. The flow ranges selected for the study are 500 25mm, 425 25mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…More than 40 kind's neutral and caustic materials and 7 kind's solid matters were produced. As the key influence factor of desulfurization efficiency and gypsum quality, it was thought that gypsum-fly ash slurry was closely related to coating aging, gypsum dehydration and desulfurization efficiency [1], studies on the performance of fly ash-lime sorbent and a small experimental research of gypsum-fly ash slurry have been reported. Tianjin Li [2] studied the potential of the sorbent-catalysts prepared from three low cost materials, i.e., the lime, fly ash and some industrial waste material containing iron oxide, have been investigated for simultaneous removal of SO 2 and NO x from flue gas in the temperature range 700-850℃.…”
Section: Introductionmentioning
confidence: 99%
“…More than 40 kind's neutral and caustic materials and 7 kind's solid matters were produced. As the key influence factor of desulfurization efficiency and gypsum quality, it was thought that gypsum-fly ash slurry was closely related to coating aging, gypsum dehydration and desulfurization efficiency [1], studies on the performance of fly ash-lime sorbent and a small experimental research of gypsum-fly ash slurry have been reported. Tianjin Li [2] studied the potential of the sorbent-catalysts prepared from three low cost materials, i.e., the lime, fly ash and some industrial waste material containing iron oxide, have been investigated for simultaneous removal of SO 2 and NO x from flue gas in the temperature range 700-850℃.…”
Section: Introductionmentioning
confidence: 99%